Cognitive Biases for Social Alcohol‐Related Pictures and Alcohol Use in Specific Social Settings: An Event‐Level Study. (11th August 2016) - Groefsema, Martine; Engels, Rutger; Kuntsche, Emmanuel; Smit, Koen; Luijten, Maartje
Abstract : Background: Alcohol use occurs mainly among friends, in social contexts, and for social reasons. Moreover, cognitive biases, such as attentional and approach biases, have repeatedly been associated with alcohol use. This study aimed to test whether nondependent drinkers display cognitive biases for social alcohol‐related (SA) pictures and whether these biases are associated with alcohol use in social drinking contexts. Methods: The visual dot probe task and stimulus–response compatibility tasks were used to measure attentional and approach biases for alcohol‐related pictures at baseline. Event‐level alcohol use was measured using Ecological Momentary Assessments via personal smartphones. One hundred and ninety‐two young adults (51.6% men; M age = 20.73) completed the study, resulting in 11, 257 assessments conducted on Thursday, Friday, and Saturday evenings for 5 consecutive weeks. Results: While no overall attentional bias for alcohol‐related pictures was found, young adults showed an approach bias for both social and nonsocial alcohol‐related pictures. Multilevel models revealed no direct association between cognitive biases for alcohol‐related pictures and alcohol use. However, higher levels of attentional bias for SA pictures were associated with more drinking when individuals were surrounded by a greater number of friends of opposite gender. Higher levels of an approach bias for SA pictures were associated with more drinking in women surrounded by a greater number of friends of the same gender. Conclusions: In a nondependent sample, cognitive biases for SA pictures could not be associated with drinking directly. However, a cognitive bias for SA pictures moderated the association between alcohol use and number of friends present. As most observed effects were gender and situation specific, replication of these effects is warranted. Abstract : This study revealed approach biases in non‐dependent drinkers, to both non‐social and social alcohol‐related pictures. These biases were not directly related to drinking in real‐life settings, however cognitive biases moderated the association between the number of friends present and alcohol use. These results suggest that implicit biases exist in non‐dependent drinkers, and that cognitive biases can have subtle effects on drinking in a social setting. As most observed effects were gender‐situation specific, replication of these effects is warranted.